Studies on shrikhand rheology - Kulkarni, C.; Belsare, N.; Lele, Ashish K. (Journal of Food Engineering, 2006)
Shrikhand, a popular Indian dessert made from yogurt, is manufactured on an industrial scale using several chemical engineering unit operations such as mixing, filtration and heat transfer. Understanding the rheology of shrikhand is not only relevant for designing large scale mixers but can also provide quantitative means for linking the microstructure of shrikhand to its perception of texture, consistency and taste. We show here that shrikhand exhibits a combination of several rheological properties such as weak gel-like viscoelasticity, an apparent yield stress, thixotropy and long structural recovery time scales. For instance, the elastic modulus is always higher than the loss modulus over the measurable frequency range and that both moduli show only weak frequency dependence that is a characteristic of gel-like consistency. Forward and reverse rate sweep tests show a distinct hysteresis loop, which is a signature of thixotropic character. In an attempt to trace the origins of these rheological properties in shrikhand we characterized its microstructure and showed that there exist two different microstructures: one composed of crystallites of milk fats having a length scale of similar to 50-100 mu m, and the other composed of aggregates of colloidal cascin micelles of similar to 0.5-10 mu m size. Our studies show that while the temperature sensitivity of the viscoelastic parameters is dominated by the semicrystalline milk fat microstructure, the shear sensitivity is largely dictated by the protein network. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Microstructure; Rheology; shrikhand